Vitamin D's role in cell proliferation and differentiation - Samuel, Sam; Sitrin, Michael D (Nutrition reviews, 2008)
Vitamin D has pleiotropic effects that go beyond its traditional role in calcium homeostasis. Hundreds of genes with vitamin D receptor response elements directly or indirectly influence cell cycling and proliferation, differentiation, and apoptosis. Vitamin D compounds also have effects on cell function that are nongenomic. The noncalcemic actions of vitamin D influence normal and pathological cell growth, carcinogenesis, immune function, and cardiovascular physiology. This review examines many of the various mechanisms by which vitamin D alters cellular growth and differentiation and explores cell‐specific factors that influence responsiveness to vitamin D.